A Stable Hexaazaoctacene Cruciform σ‐Dimer. Issue 27 (27th July 2022) - Maier, Steffen; Jester, Fabian; Hoffmann, Marvin T.; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract: Buchwald‐Hartwig coupling of a triisopropylsilyl (TIPS)‐ethynylated dibromo‐ N, N '‐dihydrotetraazapentacene with 1, 4‐bis(TIPS‐ethynyl)‐2, 3‐diaminonaphthalene furnishes a dihydrohexaazaoctacene. Its oxidation with MnO2 results in a 7, 7'‐bi(hexaazaoctacenyl). In addition to eight TIPS‐ethynyl groups, the bioctacene motif protects the azaoctacene subunits. The biazaoctacenyl displays a τ 1/2 of > 5 d in dilute solution under ambient conditions. In the crystalline state it is persistent for > 10 months. Abstract : In contrast to a triisopropylsilyl (TIPS)‐ethynylated hexaazaoctacene, its σ ‐dimer, a bihexaazaoctacenyl, is persistent in hexane and stable as a crystalline solid.